ESTIMASI KANDUNGAN KARBON TERSIMPAN SKALA PLOT PADA AGROFORESTRY POLA DUSUNG DI NEGERI HUTUMURI, KECAMATAN LEITIMUR SELATAN, KOTA AMBON - Alvanolis Ivanno Passal; Gun Mardiatmoko; Fransina Latumahina (Lambung Mangkurat University-Indonesia, 2019)
The research was carried out in the area of Forests (Agroforestry) of Dusung in Toisapu Negeri Hutumuri Hamlet, South Leitimur Subdistrict, Ambon City, continued to Pattimura University Ambon Faculty of Agriculture Technology Laboratory, Chemical and Soil Fertility Laboratory, Department of Agriculture, Hasanuddin University Makassar, South Sulawesi taken at the research location) and Pattimura University Ambon's Biochemistry Laboratory of the Faculty of Mathematics and Natural Sciences (to measure understorey litter samples taken at the research site and dried at the Technology Laboratory) and took place from August to October 2018. The study was conducted to determine the estimated carbon content stored in the scale of dusung agroforestry. Therefore, it begins with sampling at the level of the understorey, serasaf, dead wood (necromas) and topsoil. The results of the study for measurements of understorey biomass, litter (rough and fine) and dead wood, known that carbon uptake stored above the surface was 25,398.60 Kg / m² or 2,539.86 tons / ha. While the assumptions for land use systems are able to contribute to carbon absorption reserves assuming 46%, so that the value of carbon reserves in the agroforestry system is obtained and available carbon reserves of 11,683.36 tons / ha are available.